Online discussion in improving argumentation skills during last decade: A review - Setyo Admoko; Eka Putri Dian Nata Sari; Eko Hariyono; Madlazim Madlazim (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study aimed to find research trend online discussion to improve argumentation skills in education especially physics education. The method used in this research is bibliometric analysis by using VOSviewer. The data used is the Scopus database in the last 10 years. The research findings found that there are 1,447 documents that meet the predetermined criteria. The number of online discussion research increases gradually over the research period 2012-2021. The two highest sources of documents came from journals and conference proceedings and a higher percentage of citations were carried out on scientific journal. There are five trend research clusters on online discussion (4 main clusters and 1 secondary). The first cluster focuses on online discussion methods, the second cluster focuses on online discussion model, the third cluster focuses on the application of online discussions, the fourth cluster focuses on media used in online discussions, the fifth secondary cluster focuses on the goals of online discussion. The “argumentation” keyword is not included in the top 10 keywords, this shows that online discussion research has just little linked to argumentation as an indicator of the quality of online discussion. This condition creates an opportunity for further research related to online discussion in improving argumentation skills.